Cerebellar amelanotic melanoma can mimic cerebellar abscess in a pediatric case of neurocutaneous melanosis - Mormina, Enricomaria (Clin Case Rep, 2021)
Neurocutaneous melanosis (NCM) is a rare phakomatosis that may be associated with intracerebral masses. The differential diagnosis of intracerebral masses in NCM is often challenging and should include pigmented and nonpigmented lesions.